Water planning system “Agua de Honduras” used to improve Honduran investment decisions (WLE-CIAT) - CGIAR Research Program on Water, Land and Ecosystems (2018)
The Government of Honduras piloted and adopted a major new data platform, “Agua de Honduras” that provides data on hydrology, vegetative cover, soil properties, along with future climate scenarios. Implemented by the Centro Internacional de Agricultura Tropical (CIAT) and contributing to the CGIAR Research Program on Water, Land and Ecosystems (WLE), the platform has been aiding water management decisions, including being used 150 times to identify rainwater harvesting sites and influencing at least one local land investment decision.